Influence of Leadership Style and Cultural Organization on Employee Performance in the Personnel and Human Resources Development Agency of Agam District - Mayliza, Riri; Putra, Kasih Ade (Bina Bangsa International Journal of Business and Management, 2023)
One of the most important assets owned by a company is human resources because it has an influence on the survival of the company. Employees in a company should be provided with a comfortable working environtment to produce optimal performance. Leadership style is a pattern, method and expertise used by an organizational leader in acting, conveying and socializing to influence, direct, support and control other individuals or subordinates to perform a task in order to reach an agreement. Organizational culture is a comprehensive affirmation that is recognized by members of the organization in system of shared meaning. This study aims to determine the effect of leadership style and organizational culture on employee performance at Badan Kepegawaian dan Pembangunan Pembangunan Human Resources   Kabupatan Agam. Population in this study were 35 respondents who is also a sample of the entire population at the Agam District Civil Service and Human Resource Development Agency. Studies using multiple regression analysis. The results of this study indicate leadership style and organizational culture have a positive significant impact on employee performance